Mitochondria-targeted ROS scavenger JP4-039 improves cardiac function in a post-myocardial infarction animal model and induces angiogenesis in vitro - Rayane Brinck Teixeira; Jane H. Albro; Mohamed Sabra; Taslova Abedin; Aja N. Tucker; Raj Sidharth; Frank W. Sellke; Peter Wipf; M. Ruhul Abid (PLoS ONE, 2025)
Background This study aimed at evaluating the effects of JP4-039, a mitochondria-specific reactive oxygen species (mito-ROS) scavenger, on coronary angiogenesis and cardiac function in a post-myocardial infarction (MI) animal model. Methods Mice underwent ligation of the left anterior descending (LAD) artery to induce MI and received intraperitoneal (i.p.) injections of JP4-039 or vehicle (n=8 animals/group) three times/week for four weeks. Echocardiography for cardiac function and immunohistochemistry for Infarction area and capillary density were carried out. Angiogenic potential of endothelial cells (EC) was assessed by ex vivo tube formation using mouse heart EC (MHEC) and by aortic and atrial sprouting. Western blots were conducted using mouse cardiac tissue and lysates from HCAECs that were treated with or without JP4-039. Results Cardiac function including ejection fraction, fractional shortening, and fractional area change were improved significantly in JP4-039-treated animals compared to the vehicle group. JP4-039-treated hearts demonstrated significant reduction in infarction size and increased capillary density in the ischemic area. These findings were consistent with increased ex vivo endothelial sprouting of the aortae and atrial tissue from the mice treated with JP4-039. Western blots using cardiac tissue lysates from JP4-039-treated animals showed decrease in phosphorylation of AMPKα at the Threonine 172, suggesting a plausible increase in the ATP:AMP ratio. Interestingly, JP4-039 increased expression of mitochondrial complexes I and IV and increased ATP synthesis in EC. Conclusions JP4-039-mediated reduction in mito-ROS results in significantly increased coronary vascular density in ischemic myocardium, improved ATP synthesis, and recovery of post-MI cardiac function. Together, these results suggest that nitroxide nanodrug-mediated reduction in mito-ROS may help recover post-MI cardiac function.